2017
DOI: 10.1002/ejoc.201700752
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrolled Access to Benzo‐Annelated all‐cis‐ and cis,cis,cis,trans‐[5.5.5.6]Fenestranones and all‐cis‐[5.5.5.5]Fenestranes

Abstract: The synthesis of three multiply substituted fenestrindanes (all‐cis‐tetrabenzo[5.5.5.5]fenestranes) is described in detail. Depending on the stereochemical course of the twofold Michael addition of a 1,3‐indanedione to a dibenzylideneacetone in the very first step, the corresponding all‐cis‐tribenzo[5.5.5.6]fenestranones or the strained cis,cis,cis,trans isomers are obtained. In the latter case, stereochemical adjustment to the all‐cis configuration can be achieved by base‐induced epimerization. Conversion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…We have been interested in the synthesis of nonplanar π-conjugated derivatives bearing skeletal sp 3 carbons placed outside of the conjugated framework. In particular, the tetrabenzo[5.5.5.5]­fenestrane (fenestrindane) motif has been utilized to construct polyaromatic saddles. Recently, we reported that 1,4,9,12-tetraarylfenestrindanes ( 5 and 6 ) can undergo 4-fold Scholl-type heptagonal ring closure to furnish the 4-fold cove-bridged derivatives 7 and 8 , respectively (Scheme ).…”
Section: Introductionmentioning
confidence: 77%
“…We have been interested in the synthesis of nonplanar π-conjugated derivatives bearing skeletal sp 3 carbons placed outside of the conjugated framework. In particular, the tetrabenzo[5.5.5.5]­fenestrane (fenestrindane) motif has been utilized to construct polyaromatic saddles. Recently, we reported that 1,4,9,12-tetraarylfenestrindanes ( 5 and 6 ) can undergo 4-fold Scholl-type heptagonal ring closure to furnish the 4-fold cove-bridged derivatives 7 and 8 , respectively (Scheme ).…”
Section: Introductionmentioning
confidence: 77%
“…Further increase of the degree of substitution at the twelve peripheral positions of centrohexaindane appears challenging but should be possible pursuing the three established routes to the parent hydrocarbon 5. [10,28] On the one hand, it has been shown that, starting with suitably methoxy-functionalized aromatics, the construction of multiply oxy-functionalized triptindanes [32,[51][52][53] and fenestrindanes [54,55] is straightforward. Subsequent incorporation of three or, respectively, two additional anisole-or veratrole-type synthones along the propellane and fenestrane routes with multiple cyclization in the last step of the synthesis offers a number of yet unexplored pathways to, e. g., octafunctionalized derivatives of 5.…”
Section: Potential Access To Various Highly Functionalized Centrohexa...mentioning
confidence: 99%
“…Apart from purely peripheral multiple functionalization of the centrohexaindane skeleton, there are obvious possibilities to construct congeners that bear electron-rich substitutents, such as methoxy groups, in particular, at both selected outer and inner positions of the six indane wings of 5. Based on the known tetramethoxyfenestrindanes 45 [54] and 48, [55b] the fenestrane route offers a straightforward access to the hypothetical octamethoxy derivative 49, even in two complementary ways (Scheme 7). Bridgehead functionalization of 45 and 48 by established methods yielding the corresponding benzhydrylic tetra-alcohols should enable facile condension with dimethoxybenzenes and related building blocks, in analogy to the synthesis shown in Scheme 3.…”
Section: Potential Access To Various Highly Functionalized Centrohexa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ausgehend von zwei Fenestrindan-Vorstufen, 7a bzw. [19,24] Der Te traether 10 wurde dann mittels eines Überschusses an BBr 3 (8 ¾quiv.) Die Verbindungen 8 kçnnen einerseits als versteifte Derivate des o,p,o,p,o,p,o,p-Cyclooctaphenylens (9) [23] aufgefasst werden;a ndererseits stellen sie aufgrund ihrer einzigartigen Molekülgeometrie auch Zwischenstufen auf dem Wegz us attelfçrmigen Fenestran-basierten Graphenen und potenzielle Bausteine für porçse kovalente organische Gerüste dar.…”
unclassified